Antimicrobial activity of ZnO-Ag-MWCNTs nanocomposites prepared by a simple impregnation–calcination method - Rashad Al-Gaashani; Mujaheed Pasha; Khadeeja Abdul Jabbar; Akshath R. Shetty; Hussein Baqiah; Said Mansour; Viktor Kochkodan; Jenny Lawler (Scientific Reports, 2023)
Abstract Zinc oxide (ZnO) nanorods and ZnO nanostructures composited with silver (Ag) and multi-walled carbon nanotubes (MWCNTs) have been synthesized by a simple impregnation–calcination method and have been shown to be suitable for use as antimicrobial agents. The preparation method used for composite materials is very simple, time-effective, and can be used for large-scale production. Several analytical techniques, including X-ray diffraction (XRD), scanning electron spectroscopy (SEM), energy dispersive X-ray spectroscopy (EDS), transmission electron microscopy (TEM) and Fourier transmission infrared spectroscopy (FTIR), have been used to characterize the prepared ZnO-Ag-MWCNT composite materials. The effects on structural, morphological, and antimicrobial properties of (ZnO)100-x (Ag)x nanocomposites at various weight ratios (x = 0, 5, 10, 30, and 50 wt%) have been investigated. The antimicrobial properties of ZnO composited with Ag nanoparticles and MWCNTs towards both gram-positive and gram-negative bacteria species were studied. The effect of raw MWCNTs and MWCNTs composited with ZnO and Ag on the cell morphology and chemical composition of Staphylococcus aureus (S. aureus) and Escherichia coli (E. coli) was studied by SEM and EDS, respectively. It was found that composite materials made of ZnO-Ag-MWCNTs exhibit greater antibacterial activities toward the microorganisms E. coli and S. aureus than ZnO-Ag, which could be beneficial for efficient antimicrobial agents in water and air treatment applications.